'Laity as Teachers in the Ecclesia Docens'. (August 2021) - O'Collins, Gerald
Vatican II partly dismantled the separation between the hierarchy as teachers ( ecclesia docens ) and the laity as believers ( ecclesia discens ). The Council recognized the prophetic function of baptized lay persons, noting in particular the function of parents and catechists and reiterating the guidance of the Holy Spirit received by the whole church ( sensus fidei ). Special personal charisms invite recognizing the place in the ecclesia docens of many writers, artists, composers, and film directors. Their imaginative gifts have encouraged and renewed the life of faith for innumerable believers.